PEMBUATAN RESISTANT STARCH PATI BERAS DENGAN METODE ENZIMATIS DAN FISIK - Tanwirul Millati; Nurhayati Nurhayati (Jurnal Agrotek Ummat, 2020)
Rice is the leading food and a carbohydrate source for most of the world's and Indonesia population, but most rice tends to have a high glycemic index (IG). A product with a low IG is better, not only for people with diabetes but also for healthy people. Resistant starch (RS) functions as a new food ingredient that has a low glycemic index. RS is a part of starch or starch products resistant to digestion when through a gastrointestinal tract. RS has the same physiological effects as dietary fiber, can affect body weight and energy balance, increase lipid excretion to reduce calorie intake and reduce serum lipid levels, zero caloric content so that it can be used as a low-calorie food additive that can control body weight effectively. RS can be made through starch modification by physical treatment (heat treatment), chemical treatment, enzymatic treatment, and a combination of heat and enzymatic. Factors that influence RS's formation include starch properties, starch interactions with other components, processing conditions, heat processes, other treatments, and storage conditions. Therefore, the rice starch modification that contains a lot of RS needs to be known. Rice starch Hydrolysis with the dual enzyme α-amylase and pullulanase (DMT) can increase the highest RS level (51.0%) due to the increased degree of starch crystallinity. High RS results in an increase in gelatinization temperature, ΔH and phase transition temperatures, and a decrease in the speed of starch hydrolysis and weight loss.